2015
DOI: 10.1097/hjh.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Motivating patients to exercise

Abstract: The mortality risk of being inactive was equivalent to an increase of around 40  mmHg in SBP or 20  mmHg in DBP, a number relevant to hypertensive patients. Appreciating this relationship may convince the inactive to start exercising, a behavior as important as controlling BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In a study among individuals with hypercholesterolemia, Williams and Franklin found that ≥3.6 MET‐h/d of running or walking compared with ≤1.07 MET‐h/d was associated with a 37% lower risk of fatal CVD and a 26% lower risk of nonfatal CVD after adjusting for other risk factors 8. In a study of 470 163 Taiwanese adults, Li et al reported that, among hypertensive individuals, risk of mortality was 37% higher for those who were inactive compared with those who were active 6. Among participants in the Harvard Alumni Health Study, Paffenbarger et al found that men with a high level of physical activity (≥2000 kcal/wk) had lower rates of heart attack than those with a low level of physical activity (<2000 kcal/wk), even in the presence of various cardiovascular risk factors, including older age, smoking, and obesity 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study among individuals with hypercholesterolemia, Williams and Franklin found that ≥3.6 MET‐h/d of running or walking compared with ≤1.07 MET‐h/d was associated with a 37% lower risk of fatal CVD and a 26% lower risk of nonfatal CVD after adjusting for other risk factors 8. In a study of 470 163 Taiwanese adults, Li et al reported that, among hypertensive individuals, risk of mortality was 37% higher for those who were inactive compared with those who were active 6. Among participants in the Harvard Alumni Health Study, Paffenbarger et al found that men with a high level of physical activity (≥2000 kcal/wk) had lower rates of heart attack than those with a low level of physical activity (<2000 kcal/wk), even in the presence of various cardiovascular risk factors, including older age, smoking, and obesity 9.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this inverse association has been shown in various high‐risk subgroups, including older adults, current smokers, and adults with diabetes mellitus (DM), hypercholesterolemia, or hypertension 2, 3, 5, 6, 7, 8, 9, 10. Although physical activity reduces CVD risk in people with and without single CVD risk factors, it is unclear if physical activity is equally beneficial for prevention of CVD among women with varying levels of global cardiovascular risk.…”
mentioning
confidence: 99%
“…45 The mortality risk of being inactive was estimated to be equivalent to an increase of approximately 40 mm Hg in systolic blood pressure or 20 mm Hg in diastolic blood pressure, a number relevant to patients with hypertension. 46 However, it has been proven that encouraging people to be more active is not easy. 45 Additional support at the organizational level should be encouraged, and wider contextual factors that impinge on the delivery of and response to the intervention should be considered.…”
Section: Discussionmentioning
confidence: 99%